2014
DOI: 10.1186/1471-2164-15-150
|View full text |Cite
|
Sign up to set email alerts
|

Strand-specific RNA-Seq reveals widespread and developmentally regulated transcription of natural antisense transcripts in Plasmodium falciparum

Abstract: BackgroundAdvances in high-throughput sequencing have led to the discovery of widespread transcription of natural antisense transcripts (NATs) in a large number of organisms, where these transcripts have been shown to play important roles in the regulation of gene expression. Likewise, the existence of NATs has been observed in Plasmodium but our understanding towards their genome-wide distribution remains incomplete due to the limited depth and uncertainties in the level of strand specificity of previous data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
115
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(129 citation statements)
references
References 52 publications
12
115
2
Order By: Relevance
“…These numbers are in agreement with previous microarrays and RNA-Seq studies and confirm that the parasite transcriptional cascade is recapitulated at the TSS level. Furthermore, comparison of our data with a recent RNA-Seq analysis (Siegel et al, 2014) showed that the detected transcriptional initiation events correlated well with gene expression levels (Figure S4C). This suggests that the majority of these events are associated with the production of full-length transcripts.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…These numbers are in agreement with previous microarrays and RNA-Seq studies and confirm that the parasite transcriptional cascade is recapitulated at the TSS level. Furthermore, comparison of our data with a recent RNA-Seq analysis (Siegel et al, 2014) showed that the detected transcriptional initiation events correlated well with gene expression levels (Figure S4C). This suggests that the majority of these events are associated with the production of full-length transcripts.…”
Section: Resultssupporting
confidence: 77%
“…Many of these non-coding transcription units correspond to transcription initiation in an antisense orientation to coding genes. More generally, this configuration was widespread across the genome, regardless of the coding potential of the sense/antisense pairs, as previously observed (López-Barragán et al, 2011; Militello, 2005; Siegel et al, 2014). Such arrangements that presumably yield overlapping transcripts may carry a regulatory role, as shown by the expression of certain sense-antisense transcript pairs in a mutually exclusive manner.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Conversely, transcriptome sequencing data sets suggest that the majority of the genome is pervasively transcribed throughout blood stage development (3). Few Plasmodium transcription factors have been identified, with the exception of the 27 members of the Apicomplexan Apetala 2 (ApiAP2) family of transcription factors (4), which are homologous to plant AP2/ethylene response factor DNA-binding proteins, the second largest family of transcription factors in the model plant Arabidopsis thaliana (5).…”
mentioning
confidence: 99%